Pengaruh Tingkat Pendidikan, Pelatihan dan Budaya Organisasi terhadap Kinerja Pegawai Rumah Sakit Bhayangkara Kendari - Fitri Lapau; Maratun Shaleha; Al Asy Ari Adnan Hakim (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2021)
This study aims to partially analyze variables of education level, training, and organizational culture have a significant effect on employee performance, and simultaneously analyze variables of education, training, and organizational culture have a significant effect on employee performance. Type of research is a quantitative approach. Samples in this study amounted to 129 employee respondents who worked at the Bhayangkara Kendari Hospital. The analytical tool used in this research is multiple linear regression analysis. The results of this study indicate that there is a significant positive effect between training and organizational culture on employee performance at Bhayangkara Kendari Hospital, education has a positive and insignificant effect on employee performance, there is a significant positive relationship between training and employee performance, there is a significant positive relationship between organizational culture. on employee performance, for the education variable it was found that there was a positive and insignificant effect on employee performance.